COLLABORATIVE LEARNING STRATEGIES TO IMPROVE STUDENT LEARNING OUTCOMES - Siti Norsaniyah; Jazilurrahman Jazilurrahman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This research aims to determine the forms of collaborative learning strategies in improving student learning outcomes, apart from that it also aims to provide a comprehensive picture of the forms of collaborative learning strategies and the results of the process of implementing collaborative learning strategies. This research method uses a qualitative case study type approach. Data was collected through participant observation, in-depth interviews and documentation analysis. Data analysis was carried out through the stages of data reduction, data presentation and drawing conclusions. To ensure that the data found was relevant, researchers checked the validity of the data by means of extended observations, persistence of observations, and triangulation. The findings of this research prove that the use of audio-visual media in collaboration with the use of demonstration methods can increase learning interest, enthusiasm for learning and student learning outcomes both in the cognitive, affective and psychomotor aspects of understanding. The implication is that institutions within the Islamic boarding school environment can develop effective and efficient learning models, combining with sophisticated technology to increase students' understanding and to achieve the goals of learning and education effectively and efficiently without destroying local culture, religious values and Islamic boarding school values.